Web-Based Applications in Calculation of Family Heritage (Science of Faroidh) - Ilka Zufria, M. Hasan Azhari (Query: Journal of Information Systems, 2017)
Separating of inheritance according in sciences of faroidh each heir does not get the same part depending on their relationship to the inheritance recipient. This is because the needs of each heir are different, such as heirs of boys and girls differ the reason boys have a big responsibility and if already married  should have been obliged to offer for his family while the daughter if already have family responsible for the necessities of life. In addition, in sciences of faroidh also there is a hijab or a barrier where heir can get a share can also not get a part depending on whether the heirs prevented it causing its own complexity in the calculations. Nowadays it is very difficult to meet people who understand about this division of inheritance. Just little of people are experts distribute inheritance based on faroidh. So created a web-based application to aid in the calculation and distribution of inheritance properly and managed computerized that can ease people in solving this problem.